Insights into the Associations Between Systolic Left Ventricular Rotational Mechanics and Left Atrial Peak Reservoir Strains in Healthy Adults from the MAGYAR-Healthy Study - Attila Nemes; Árpád Kormányos; Nóra Ambrus; Csaba Lengyel (Biomedicines)
Introduction: In systole, when the left ventricle (LV) twists, the left atrium (LA) behaves like a reservoir, having a special wall contractility pattern opposite to that of the LV wall. Accordingly, the objective of the present study was to investigate the associations between LV rotational mechanics and LA peak (reservoir) strains as assessed simultaneously by three-dimensional speckle-tracking echocardiography (3DSTE) under healthy conditions. Methods: In the present study, 157 healthy adults (mean age: 33.2 ± 12.7 years, 73 men) were involved. Complete two-dimensional Doppler echocardiography with 3DSTE-derived data acquisition were performed in all cases. The 3DSTE-derived LV rotational and LA strain parameters were determined at a later date. Results: Global LA peak reservoir circumferential (22.7 ± 6.4% vs. 27.6 ± 6.8%, p < 0.05) and area (57.8 ± 20.0% vs. 66.0 ± 22.7%, p < 0.05) strains proved to be reduced in the case of the highest vs. lowest basal LV rotation; other LA peak reservoir strains were not associated with increasing basal LV rotation. Global LA peak radial strain was highest in the case of the lowest vs. highest apical LV rotation (−19.2 ± 9.4% vs. −13.0 ± 8.2%, p < 0.05). Global LA peak reservoir 3D strain was lowest in the case of the highest vs. lowest apical LV rotation (−9.9 ± 6.8% vs. −5.0 ± 4.2%, p < 0.05). Only apical LV rotation proved to be significantly reduced in the case of the highest vs. lowest global LA peak reservoir 3D strain (8.12 ± 3.23° vs. 10.50 ± 3.44°, p < 0.05). Other global LA peak reservoir strains were not associated with basal and apical LV rotations. Conclusions: In LV systole, LV rotational mechanics is associated with LA deformation represented by LA peak (reservoir) strains even in healthy circumstances. While basal LV rotation is associated with LA widening, apical LV rotation is associated with LA thinning, suggesting the close cooperation of the LV and LA in systole even in healthy adults.